PENGARUH GREEN MARKETING DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN PADA SUPERINDO CITY MALL KOTA SUKABUMI - Sopian, Riana; Sobar, Agus (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2024)
This study aimed to determine the effect of green marketing on customer loyalty at Super Indo City Mall Sukabumi and the effect of brand image on customer loyalty at Super Indo City Mall Sukabumi. In this study, the author's research method is quantitative. The population in this study were consumers of Super Indo City Mall Sukabumi. This study's sample was Super Indo Sukabumi consumers, totaling 99 people. The type of data used in this study is primary data by distributing questionnaires to respondents. Analysis methods with validity and reliability tests of instruments. Prerequisite analysis tests include a data normality test, multicollinearity test, heteroscedasticity test, and linearity test, then the analysis technique uses multiple regression. The variables used are Green Marketing and Brand Image variables as independent variables and Customer Loyalty as the dependent variable. Multiple linear regression models with the results of the equation Y = 7.948 + 0.478 + 0.422. From these results the constant is 7.948, Green Marketing (X1) is 0.478 or 4.78% and Brand Image (X2) is 0.422 or 4.22%. Green Marketing (X1) t-test results with significant t-test results <0.05, namely (0.000 <0.05), so there is a partial influence. Brand Image (X2) t test results with significant results of the t-test <0.05, namely (0.000 <0.05), so there is a partial influence. Green Marketing and Brand Image simultaneously have a positive and significant effect on Super Indo Customer Loyalty at City Mall Sukabumi City as evidenced by the results of the significant F test in the ANOVA test found that the F-count value is 39.343. With a significant value of 0.000 and an F-table value of 3.94, it can be concluded that F-count> F-table with a significant level of 0.000 <0.05.